Analisis Pemberdayaan UMKM Melalui Pemanfaatan Car Free Day Terhadap Peningkatan Kesejahteraan Masyarakat Di Kabupaten Sumbawa - Yayuk Yayuk; Fahlia Fahlia (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of Car Free Day (CFD) utilization on UMKM empowerment, the effect of Car Free Day (CFD) utilization on community welfare, the effect of UMKM empowerment on community welfare, and the mediat-ing role of UMKM empowerment in the relationship between Car Free Day (CFD) utilization and community welfare in Sumbawa Regency. This research employed a quantitative approach with an explanatory method. The population consisted of UMKM actors participating in the Samota Car Free Day in Sumbawa Regency, with a sample of 60 respondents selected using the Slovin formula. Data were col-lected through questionnaires using a Likert scale and analyzed using path analysis and the Sobel test with the assistance of SPSS software. The results indicate that Car Free Day (CFD) utilization has a positive and significant effect on UMKM empowerment. Furthermore, Car Free Day (CFD) utilization has a positive and significant effect on community welfare. In contrast, UMKM empowerment has a negative and insignificant effect on community welfare. The Sobel test also shows that UMKM empowerment is not able to mediate the effect of Car Free Day (CFD) utilization on community welfare. These findings suggest that improving the utili-zation of Car Free Day (CFD) can directly enhance community welfare, while the existing UMKM empowerment programs have not yet provided an optimal contri-bution to improving community welfare.